Analisis EVA, MVA, dan Tobin’s Q Terhadap Harga Saham Emiten di BEI Periode 2012-2016 - Stevi Jimry Poluan; Rony Joyo Negoro Octavianus; Edwin Aditya Prabowo (Universitas Katolik Soegijapranata, Semarang, 2019)
This study aims to analyze the effect of EVA, MVA, and Tobin’s Q on share price of listed companies in IDX. The type of research used on this study is assosiative research with quantitative approach. Sampling method used is purposive sampling. Multiple Linear Regression used to analyze the data. The results showed that EVA had no effect to companies’ stock prices and MVA had positive and significant effect to companies’ stock prices, and Tobin’s q had positive and significant effect to companies’ stock prices.